Applying The Concept Of Green Cities In Nigeria: Challenges And Prospects - Ekong, Faith U. (Advances in Social Sciences Research Journal, 2017)
One of the most pressing issues in Nigeria today is rapid urbanisation and its impacts. The environmental sustainability of cities in Less Developed Countries generally has been a key concern and the concept of “Green Cities” is being promoted as a response. Urban planners have been at the forefront in implementing the green city agenda in developed countries. In Nigeria, it remains essentially a concept. This concept is only discussed in seminar and conference papers but definitive action is lacking. There has been no policy response either at national or state levels to implement the green city agenda. This is inspite of the obvious climate change effects – excessive flooding and the environmental challenge manifested in failed refuse disposal systems in cities across the country, lack of open spaces, overcrowding and development of unplanned neighbourhoods. The paper will address these questions, is the green concept relevant to Nigeria; what are the challenges in implementing the green agenda in Nigeria, what policy programme responses are needed to apply the concept in Nigerian cities and what will be the specific role of planners?